Relationship Between Potential Antihypertensive Drug Interactions and Target Blood Pressure in Outpatients with Chronic Kidney Disease - Hidiyaningtyas, Lutfi; Lestari, Mardiana; Puspitasari, Trinita (Universitas Ahmad Dahlan, 2025)
Background: Chronic kidney disease (CKD) is an increasingly prevalent condition globally and is strongly associated with cardiovascular disease (CVD). Hypertension frequently occurs during the development of kidney disease and is a leading cause of its progression. CKD patients with complications and comorbidities often require combination therapy. However, some drug combinations can cause adverse drug reactions and reduce the efficacy of therapy. One such reaction is failing to achieve the blood pressure target; Method: This research is a non-experimental, analytical study with retrospective sampling. The sample for this study consisted of 71 patients. Potential drug interactions were analyzed using the drug interaction checker application on drug.com. Univariate analysis was performed to describe patient characteristics, and bivariate analysis using the Chi-square statistical test was performed to examine the relationship between the potential interactions of antihypertensive drugs and blood pressure targets; Results: The correlation analysis test results showed no relationship between the potential interaction of antihypertensive drugs and the target blood pressure of CKD patients (p-value = 0.607); Conclusion: There is potential for antihypertensive drug interactions in CKD patients, but they do not statistically affect blood pressure targets.